Influence of Quality Management on the Innovative Performance - Cabral Marques Fernandes, António Augusto; Lourenço, Luís António Nunes; Silva, Maria José Aguilar Madeira (Review of Business Management, 2014)
The relationship between total quality management (TQM) and innovation has been studied in several investigations. However, there is some disagreement among the researchers. Many authors suggest that the impact of TQM on innovation depends both on the TQM dimensions considered and on the type of innovation. This paper aims at identifying elements of TQM as determinants of innovation outputs of organizations. The conceptual model proposed considers 8 TQM variables (leadership; customer focus; involvement and development of people; management by processes; continuous improvement; relations with suppliers; measuring results; product design) as factors that can have impact on 6 innovation outputs (research, development and technological innovation; product innovation; process innovation; organizational innovation; management innovation; marketing innovation). This study is based on empirical data collected through a questionnaire answered by 218 ISO 9001:2008 certified organizations. Generally, it is possible to conclude that the adoption of TQM principles plays a key role in innovation activities. The investigation has interesting practical implications practice. Therefore, the adoption of certain organizational principles can encourage the development of innovation.